Prevalence and Factors Affecting Discrimination Towards People Living With HIV/AIDS in Indonesia - Rimawati Aulia Insani Sadarang (Korean Society for Preventive Medicine, 2022)
Objectives This study aimed to identify the behaviors associated with discrimination towards people living with HIV/AIDS (PLHA) in Indonesia and to determine the factors affecting discrimination. Methods Secondary data from the 2017 Indonesia Demographic and Health Survey were analyzed using a cross-sectional design. Discrimination was assessed based on the questions (1) "Should children infected with HIV/AIDS be allowed to attend school with non-infected children?" and (2) "Would you buy fresh vegetables from a farmer or shopkeeper known to be infected with HIV/AIDS?" Multivariable logistic regression was used to determine the factors affecting discrimination, with adjusted odds ratio (aOR) and 95% confidence interval (CIs) used to show the strength, direction, and significance of the associations among factors. Results In total, 68.9% of 21 838 individuals showed discrimination towards PLHA. The odds of discrimination were lower among women (aOR, 0.63; 95% CI, 0.55 to 0.71), rural dwellers (aOR, 0.81; 95% CI, 0.75 to 0.89), those who understood how HIV is transmitted from mother to child (aOR, 0.81; 95% CI, 0.73 to 0.89), and those who felt ashamed of their own family's HIV status (aOR, 0.56; 95% CI, 0.52 to 0.61). The odds were higher among individuals who knew how to reduce the risk of getting HIV/AIDS (aOR, 1.27; 95% CI, 1.15 to 1.39), how HIV/AIDS is transmitted (aOR, 3.49; 95% CI, 3.09 to 3.95), and were willing to care for an infected relative (aOR, 2.78; 95% CI, 2.47 to 3.13). A model consisting of those variables explained 69% of the variance in discrimination. Conclusions Gender, residence, knowledge, and attitudes related to HIV/AIDS were explanatory factors for discrimination against PLHA. Improvements in HIV/AIDS education programs are needed to prevent discrimination.